Metabolic and Microbial Dysregulation in Preterm Infants with Neonatal Respiratory Distress Syndrome: An Early Developmental Perspective - Bi, Yanxu; Yu, Wenyi; Bian, Wenjie; Jin, Mengtong; He, Yukun; Wang, Jinglei; Miao, Xiaofeng; Guo, Tiantian; Ma, Xiaojun; Gong, Pihua; Li, Ran; Xi, Jiangli; et al. (Journal of proteome research, 2024)
Neonatal respiratory distress syndrome (NRDS) is one of the most severe respiratory disorders in preterm infants (PTIs) due to immature lung development. To delineate the serum metabolic alterations and gut microbiota variations in NRDS and assess their implications on neonatal development, we enrolled 13 NRDS neonates and 12 PTIs and collected fecal and serum specimens after birth. Longitudinal fecal sampling was conducted weekly for a month in NRDS neonates. NRDS neonates were characterized by notably reduced gestational ages and birth weights and a higher rate of asphyxia at birth relative to PTIs. Early postnatal disturbances in tryptophan metabolism were evident in the NRDS group, concomitant with elevated relative abundance of Haemophilus, Fusicatenibacter, and Vibrio. Integrative multiomics analyses revealed an inverse relationship between tryptophan concentrations and Blautia abundance. At one-week old, NRDS neonates exhibited cortisol regulation anomalies and augmented hepatic catabolism. Sequential microbial profiling revealed distinct gut microbiota evolution in NRDS subjects, characterized by a general reduction in potentially pathogenic bacteria. The acute perinatal stress of NRDS leads to mitochondrial compromise, hormonal imbalance, and delayed gut microbiota evolution. Despite the short duration of NRDS, its impact on neonatal development is significant and requires extended attention.